The Effect of Tapping on Functional Changes in Spinal Mobility and Respiratory System in Adolescents with Idiopatic Scolosis: Pilot Study - Ilona Čeponkienė; Vaida Aleknavičiūtė-Ablonskė (Lithuanian Sports University, 2022)
Background. Scoliosis affects spinal mobility and the respiratory system. The Schroth method is an effective tool for the treatment of scoliosis. However, there is insufficient evidence for the efficiency of kinesio taping with the Schroth method to help manage the condition of spinal mobility and respiratory system changes for adolescents with idiopathic scoliosis. The aim. To evaluate the efficacy of the Schroth method and the Schroth method in combination with kinesio taping for spinal mobility and functional changes in the respiratory system in adolescents with idiopathic scoliosis. The methods. The study included 8 adolescent volunteers diagnosed with idiopathic scoliosis. The adolescents were divided into two groups. The Schroth method was used for the first group and the Schroth method with kinesiology taping for the second group. The study lasted 2 months, and both groups underwent 2 interventions per week. Both before and after the interventions, participants were assessed for trunk functional stability (Mathias test), lumbar and thoracic spine mobility (Schober and Otto tests), vital lung capacity (VC), and forced expiratory capacity in 1 s (FEV1). The results. In the analysed results of the interventions, it was found that the Mathias test, the Schober and Otto test, the VC and the FEV1 were improved in both groups. Comparing the results between the groups, it was established that the spinal mobility was better (p < 0,05) in the second group. However, lumbar and thoracic spinal mobility, VC, FEV1 were better (p<0,05) in the first group. The conclusion. The Schroth method with and without kinesiological taping increased trunk stability, spinal cord mobility, and VC and FEV1. The Schroth method with kinesio taping is more effective for trunk functional stability, however only the Schroth method is more effective with mobility of the lumbar and thoracic spine part as well as for VC and FEV1. Keywords: spinal cord mobility, trunk functional mobility, vital capacity.